CSF Neurofilament Light Chain but not FLT3 Ligand Discriminates Parkinsonian Disorders - Herbert, Megan K.; Aerts, Marjolein B.; Beenes, Marijke; Norgren, Niklas; Esselink, Rianne A. J.; Bloem, Bastiaan R.; Kuiperij, H. Bea; Verbeek, Marcel M. (Frontiers in Neurology, 2015)
The differentiation between multiple system atrophy (MSA) and Parkinson’s disease (PD) is difficult, particularly in early disease stages. Therefore, we aimed to evaluate the diagnostic value of neurofilament light chain (NFL), fms-like tyrosine kinase ligand (FLT3L) and total tau protein (t-tau) in cerebrospinal fluid (CSF) as biomarkers to discriminate MSA from PD. Using commercially available enzyme-linked immunoassays (ELISAs), we measured CSF levels of NFL, FLT3L and t-tau in a discovery cohort of 36 PD patients, 27 MSA patients and 57 non-neurological controls and in a validation cohort of 32 PD patients, 25 MSA patients, 15 PSP patients, 5 CBS patients, and 56 non-neurological controls. Cut-offs obtained from individual assays and binary logistic regression models developed from combinations of biomarkers were assessed. CSF levels of NFL were substantially increased in MSA and discriminated between MSA and PD with a sensitivity of 74% and specificity of 92% (AUC = 0.85) in the discovery cohort and with 80% sensitivity and 97% specificity (AUC = 0.94) in the validation cohort. FLT3L levels in CSF were significantly lower in both PD and MSA compared to controls in the discovery cohort, but not in the validation cohort. T-tau levels were significantly higher in MSA than PD and controls. Addition of either FLT3L or t-tau to NFL did not improve discrimination of PD from MSA above NFL alone. Our findings show that increased levels of NFL in CSF offer clinically relevant, high accuracy discrimination between PD and MSA.